Analisis Faktor-Faktor Yang Mempengaruhi Hasil Belajar Kognitif, Afektif, Dan Psikomotorik Siswa Pada Mata Pelajaran Ekonomi - Harlin, Lalu Wira Banu; Susilawati, Susilawati (Alpatih Harapan Semesta, 2024)
This study aims to find out the factors that affect the cognitive, affective and psychomotor learning outcomes of students in Economics subjects of class X students of Al-Bdiyah Islamic High School. The research method used in this study is qualitative research using a descriptive approach. Data sources are collected through primary data and secondary data. The data collection techniques and instruments in this study use interviews, observations and documentation. Based on the results of the study, it was shown that cognitive factors were related to students' understanding of concepts and analytical abilities which were influenced by the teaching methods used. Students understand the importance of distinguishing between needs and desires in managing finances. Affective factors, motivation and interest in economics play an important role, influenced by support from teachers and parents. Psychomotor factors are influenced by students' opportunities to engage in practical activities, which can improve their skills and application of theories in the context of daily life.